The Century-Long Journey of Peptide-Based Drugs - José R. Almeida (MDPI AG, 2024)
The pioneering medical application of peptides as therapeutics began approximately a century ago; however, they remain clinically relevant candidates garnering more attention on the drug development agenda [...]